Beyond Usual Care: A Multidisciplinary Approach Towards the Treatment of Obstructive Sleep Apnoea - Arachchige, Miuni Athauda; Steier, Joerg (Frontiers in Cardiovascular Medicine, 2022)
Obstructive Sleep Apnoea (OSA) is common and characterised by repeated apnoeas and hypopnoeas while asleep due to collapse of the upper airway. OSA can have a significant impact on physical and mental health and, when left untreated, is associated with increased risk of developing cardiovascular ill health. Besides cardiorespiratory implications excessive daytime sleepiness, morning headaches, limited memory function and lack of concentration are some further symptoms caused by OSA. Continuous Positive Airway Pressure (CPAP) therapy is the evidence-based treatment to maintain upper airway patency in patients with moderate to severe OSA. Proper adherence to CPAP therapy successfully abolishes nocturnal apnoeas and hypopnoeas, and diminishes consequences of uncontrolled OSA, such as treatment resistant hypertension. However, long term adherence to CPAP remains an unresolved limitation of this method. Although alternatives to CPAP therapy may be less efficacious, there is a variety of non-CPAP treatments that includes conventional lifestyle advice, postural advice, the use of mandibular advancement devices (MADs), surgical treatment options, such as uvulopalatopharyngoplasty, tonsillectomy, or maxillomandibular advancement, and the use of electrical stimulation of the upper airway dilator muscles. Hypoglossal Nerve Stimulation is available as an invasive (HNS) and a transcutaneous (TESLA) approach. For the management of “difficult-to-treat” patients with OSA, particularly in those in whom first line therapy proved to be unsuccessful, a multidisciplinary team approach may be helpful to incorporate the available options of non-CPAP therapy and provide appropriate choices. Symptom control, patient-related outcome measures and long-term cardiovascular health should be prioritised when choosing long-term therapies to treat OSA. The inclusion of patients in the choice of successful management options of their condition will facilitate better long-term adherence. Advancing clinical trials in the field will further help to resolve the relative lack of evidence for effective non-CPAP methods.